Indigenous People and Smallpox in Argentina's Desert Campaign, 1879–1881. - Christensen, Robert (Ethnohistory, 2024)
Argentina's 1879–85 Desert Campaign formed the basis for dispossessing the Indigenous community of its southern frontier. This article argues that the Desert Campaign should be understood as much as an epidemiological event as a military one, focusing on the most intense phase of a smallpox epidemic that ravaged communities of Indigenous survivors. More lives were lost to smallpox than to combat, particularly as the disease permeated prisoner camps. A general lack of concern for the health of Indigenous prisoners punctuated their experience of dispossession at the hands of the Argentine army and "distribution" into forced labor systems throughout the country.